Utilization of Nanotechnology in Metformin Delivery: The Morphometric Study of Pancreatic Islets of Diabetic Rat Model - Pakaya, David; Fahira, Aliyah Rezky; Anwar, Sarifuddin; Lintin, Gabriella Bamba Ratih (Universitas Negeri Gorontalo, 2024)
Introduction: In diabetic conditions, damage of β cells and changes the structure of pancreatic islets was exhibited. Metformin can improve this condition. The nanoparticle form of metformin can improve bioavailability and accelerate cell regeneration, and pancreatic islets can be repaired. The aim of this study to know the effect of nanoparticles metformin on fasting blood glucose levels and pancreatic islet morphometry in diabetic rat models.Method: An experimental research with posttest-only controlled group design was conducted on 16 white male Wistar rats. The streptozotocin (STZ) 40 mg/kgBB were injected i.p. Rats were divided into four groups: K1: normal control; K2: negative control (diabetes model); K3: diabetes model treated with metformin 100mg/kgBB; K4: diabetes model treated with nanoparticle metformin 100mg/kgBB. The body weight and fasting blood glucose levels were measured periodically. The histology of pancreatic islets was performed with hematoxylin-eosin staining and quantified using ImageJ software. The data were analyzed with GraphPad Prism 8.0.0 using nonparametric Kruskal-Wallis test.Results: Metformin therapy decreased the fasting blood glucose levels in K3 starting on day 21 and K4 starting on day 7, but there was no statistical difference (p=0.0597). Pancreatic islet morphometry showed the pancreatic islet area was found to be statistically different (p=0.026), and the perimeter was not statistically different (p=0.115).Conclusion: Metformin nanoparticle form decreased the fasting blood glucose levels and effectively improved the area and perimeter of pancreatic islets of the diabetic rats model, but the perimeter of the pancreatic islets is not statistically significant.Keywords: Diabetes, metformin, nanoparticles, pancreatic islets, morphometry.